Public Expenditure in Nepal: A Case of Transportation Sector - Ghimire, Narayan Prasad (Journal of Management and Development Studies, 2021)
The rapid growth in public investment in various sectors was assumed after decades of conflict and an unstable political situation. With the declaration of the Federal Republic, Nepal is going to embark on accelerated economic growth. This has somewhat caused concerns among policymakers of its implication for economic growth. And the government investment in transportation infrastructure is one of the core strategies, called the ‘infrastructure of infrastructures’. The main aim of this study is, therefore, to explain the relationship between economic growth and public expenditure in the transportation sector in Nepal. Primarily, this study has focused on the distinction of expenditures in the five-year development plans in three systems (Panchayat, Democratic, and Republic). This study used time series data collected between 1975 and 2016. The statistical and econometric tools have been used for the study. The result shows that the trend of government investment on public expenditure has increased in the Republic system. This study reveals that the variables are stationary on the first difference. The obtained regression model is satisfactory by diagnostic tests (errors are normally distributed, no serial correlation, and homoscedastic). The data explain the positive and significant influence of Transportation Capital Expenditure on Gross Domestic Product, and, hence, it is contributing to economic growth. Furthermore, the results show short-run unidirectional causation from Transportation Capital Expenditure to Gross Domestic Product.